The Effect of Financial Knowledge on Financial Literacy with Mediated by Financial Behavior in Society of Palembang City South Sumatera - YULIANI YULIANI (MIX: JURNAL ILMIAH MANAJEMEN, 2019)
The Indonesian financial literacy index is still very low. This low index makes the government through the Financial Services Authority (OJK) make a strategy contained in the Indonesian National Financial Literacy Strategy or SNLKI (Revisit 2017). The strategy is expected that the Indonesian people have the knowledge and skills and beliefs that are reflected in attitudes and behaviors regarding financial management and are able to take quality financial decisions for Financial Well Being. The research objective is to analyze the direct effect of financial knowledge on financial literacy. Analyzing the indirect influence of financial behavior as a mediator of the effect of financial knowledge on financial literacy. Non-probability of purposive sampling technique as many as 105 respondents. Data collection conducted in May-June 2019. The data used is primary using the research instrument in the form of a questionnaire with a 5-point Likert scale measurement. Data was collected by distributing questionnaires both directly and online questionnaires through a Google questionnaire. Data analysis techniques are descriptive and inferential. Inferential testing using Structural Equation Modeling (SEM). The research findings are that there is a direct influence of financial knowledge on financial literacy. The indirect influence of financial behavior on financial literacy is not significant so financial behavior is not mediation.